Method for producing liquid crystal polymer web

The method of slurry preparation, spray drying, and deposition addresses the challenges of manufacturing LCP films by achieving uniform dispersion and incorporation of fine fibers and solid materials, resulting in high-quality LCP webs.

JP7666595B2Active Publication Date: 2025-04-22MURATA MFG CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023527548
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-06-07
Filing Date
2022-04-07
Publication Date
2025-04-22
Estimated Expiration
2042-04-07

AI Technical Summary

Technical Problem

Existing methods for manufacturing liquid crystal polymer (LCP) films face challenges such as uneven dispersibility, viscosity mismatch, agglomeration, and difficulty in incorporating fine fibers and solid materials due to issues like clogging and poor airflow control.

Method used

A method involving slurry preparation, spray drying, and deposition to manufacture LCP webs using fine LCP fibers, which allows for uniform dispersion and incorporation of solid materials without the limitations of traditional methods.

Benefits of technology

This method enables the easy production of LCP webs with high dispersion uniformity, reducing the risk of agglomeration and clogging, and allowing for the use of fine fibers and solid materials effectively.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007666595000001
    Figure 0007666595000001
  • Figure 0007666595000002
    Figure 0007666595000002
  • Figure 0007666595000003
    Figure 0007666595000003
Patent Text Reader

Abstract

A method for producing a liquid crystal polymer web according to the present invention comprises: a slurry preparation step for preparing a slurry which contains a dispersion medium and liquid crystal polymer fibers that are dispersed in the dispersion medium; a spray drying step in which the slurry is sprayed, and the sprayed slurry is dried by means of a gas for drying; and a deposition step for forming a web by depositing the spray-dried liquid crystal polymer fibers.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a liquid crystal polymer web. [Background technology]

[0002] In high-frequency FPC boards, liquid crystal polymer (LCP) is used as the main material, but there is a demand for further reduction in dielectric constant, and for example, the addition of low-dielectric resin materials such as fluororesin to LCP is being considered. In this case, it is desirable to add fluororesin powder. In addition to fluororesin, there is also a strong demand for adding functional fillers to LCP to impart various functions.

[0003] Conventional LCP films are produced by melt extrusion, but when fillers are mixed into LCP using the melt extrusion method, problems arise such as differences in dispersibility and viscosity, gas generation and corrosion due to decomposition, and holes in the film when stretched (Patent Document 3: JP 2019-65061 A).

[0004] It is also possible to prepare a web of LCP fibers, press it, and solidify it to make it into a film. As a method for preparing a web, a method has been proposed in which LCP is made into fibers, slurried, and made into a wet web. In addition, as in Patent Document 2 (JP Patent Publication 2003-129392 A), it has also been proposed to mix a filler into it. If the LCP is made into a finer fiber form than that in Patent Document 2, it may be possible to heat press the web of LCP mixed with the filler into a thin film.

[0005] Other known web production methods include dry methods such as the carding method and the air-laying method.

[0006] In the carding process, fibers cut to lengths of about 1 to 10 cm are formed into a thin continuous web using a card or air randomizer.

[0007] In the airlaid method, first, a pulp sheet or short fibers (synthetic fibers, etc.) with a length of about 3 to 12 mm, called short cut or chopped fibers, are mechanically defibrated in a dry process. The defibrated short fibers are deposited on a wire mesh that travels using air as a medium to form a continuous web.

[0008] As another method that applies the airlaid method, for example, a method for manufacturing a web sheet disclosed in Patent Document 1 (JP Patent Publication No. 2018-145574) is known. In this method, fibers are sorted using a cylindrical sieve that is rotated, and the sorted fibers are dispersed again using a cylindrical sieve that is rotated. The dispersed fiber powder is deposited on a mesh belt while being sucked by a downflow, thereby manufacturing a web sheet. Patent Document 1 describes that the average diameter of the fibers used to manufacture the web sheet is 1 μm or more and 1000 μm or less, and the length of the fibers is 1 μm or more and 5 mm or less. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] JP 2018-145574 A [Patent Document 2] JP 2003-129392 A [Patent Document 3] JP 2019-65061 A Summary of the Invention [Problem to be solved by the invention]

[0010] Representative methods for producing LCP films include melt extrusion (horizontal stretching) and melt extrusion (inflation). When compounding with fluororesin using this method, the temperature dependence of the melt viscosity of LCP, which is a rod-shaped polymer, is different from that of normal random coil polymers, so the viscosity of LCP and the viscosity of fluororesin in the molten state do not match, and compatibility with fluororesin is low. For this reason, the fluororesin forms aggregates, making it difficult to disperse uniformly in the LCP.

[0011] One way to solve this problem is through the papermaking process. With the papermaking process, the fluororesin does not become molten, so there is no aggregation of the fluororesin due to the difference in viscosity between the LCP and the molten fluororesin. However, because fluororesin has low hydrophilicity, it cannot be suspended in a dispersion medium containing water, which can disperse the fibrous LCP.

[0012] It is possible to disperse hydrophobic fibers, etc. in water by adding a dispersant such as a surfactant to the water, but the surfactant remains in the web even after drying and may have a negative effect on the electrical properties of the web for electronic components.

[0013] It is also possible to make a slurry of hydrophobic fibers by adding a large amount of organic solvent to the dispersion medium, but in the case of papermaking, it is necessary to use a dilute dispersion of about 0.1%, which requires the use of a large amount of organic solvent, resulting in safety issues and increased manufacturing costs.

[0014] On the other hand, in the case of dry methods, the dispersibility of fluororesin in water is not an issue. For this reason, for example, it is possible to mix LCP fine fibers with fluororesin using an air-laying method, but LCP fine fibers tend to form aggregates when dried, making it difficult to pass through a sieve or disperse in air.

[0015] In addition, the carding method generally does not allow for the use of short fibers of 20 mm or less. In the airlaid method, short fibers of 20 mm or less can be used, but fibers with a length (longitudinal dimension) of a few mm or less cannot be used.

[0016] The method described in Patent Document 1 can be used with fibers on the order of microns, and furthermore, the fibers are more uniformly dispersed in the obtained web than in the carding method or airlaid method.

[0017] However, in the method described in Patent Document 1, the fibers are selected and dispersed using a sieving mechanism in the air. Therefore, when using fine fibers that are easily charged, such as crushed liquid crystal polymer fibers (LCP fibers), there is a problem that the fibers are highly cohesive and do not pass through the sieve, which tends to cause clogging. In addition, since fiber aggregates are likely to occur, the uniformity of fiber dispersion in the web decreases. Note that if the size of the sieve openings is reduced in order to improve the uniformity of fiber dispersion, clogging becomes even more likely to occur.

[0018] Furthermore, in the method described in Patent Document 1, it is necessary to control the airflow to deposit the fibers on the mesh belt, but the smaller the fiber size, the more likely it is to aggregate, making it difficult to disperse the fibers uniformly with the airflow.

[0019] Furthermore, when multiple types of materials are combined to be used as the web material, the dry method involves dispersing different powders in the air, but since the stirring force is weaker than in the wet method, it is difficult to uniformly disperse powders other than the liquid crystal polymer fibers.

[0020] In view of the above problems, an object of the present invention is to provide a method for easily producing a liquid crystal polymer web using fine liquid crystal polymer fibers.

[0021] Another object of the present invention is to provide a method for producing a web comprising a composite of liquid crystal polymer fibers and a solid material different from the liquid crystal polymer fibers. [Means for solving the problem]

[0022] The method for producing a liquid crystal polymer web according to the present invention includes the steps of: A slurry preparation step of preparing a slurry containing a dispersion medium and liquid crystal polymer fibers dispersed in the dispersion medium; a spray drying step of spraying the slurry and drying the sprayed slurry with a drying gas; depositing the spray dried liquid crystalline polymer fibers to form a web. Effect of the Invention

[0023] According to the present invention, a liquid crystal polymer web can be easily produced by using fine liquid crystal polymer fibers.

[0024] In one embodiment of the present invention, a web can be produced that is a composite of liquid crystal polymer fibers and a solid material different from the liquid crystal polymer fibers. [Brief description of the drawings]

[0025] [Figure 1] FIG. 2 is a flow chart showing a manufacturing process of a liquid crystal polymer web according to an embodiment. [Diagram 2] 1 is a schematic diagram for explaining a manufacturing process of a liquid crystal polymer web according to an embodiment. [Diagram 3] 1 is a schematic diagram for explaining a manufacturing process of a liquid crystal polymer web according to an embodiment. [Figure 4] 1 is a schematic diagram for explaining a manufacturing process of a liquid crystal polymer web according to an embodiment. [Diagram 5] 3 is a photograph showing the cross section of a liquid crystal polymer web in Example 1 and Comparative Example 2. [Figure 6] 1 is a photograph of a dispersion liquid in a confirmation test of a dispersion medium with low dispersibility. [Figure 7] 3 is a cross-sectional photograph of the composite web of Example 2. [Figure 8] 1 is a cross-sectional photograph of a film obtained by pressing the composite web of Example 2. [Figure 9] 1 is a cross-sectional photograph of the composite web of Example 3. [Figure 10] 1 is a cross-sectional photograph of the composite web of Example 4. [Figure 11] 1 is a cross-sectional photograph of the film of Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] Hereinafter, a method for producing a liquid crystal polymer (fine fiber) web according to one embodiment of the present invention will be described.

[0027] <<Method of manufacturing liquid crystal polymer web>> As shown in FIG. 1, the method for producing a liquid crystal polymer web according to this embodiment includes at least a slurry preparation step (S1), a spray drying step (S2), and a deposition step (S3).

[0028] In the slurry preparation step (S1), a slurry containing a dispersion medium and liquid crystal polymer fibers dispersed in the dispersion medium is prepared.

[0029] In the spray drying step (S2), the slurry is sprayed, and the sprayed slurry is dried with a drying gas.

[0030] In the depositing step (S3), the spray dried liquid crystalline polymer fibers are deposited to form a web.

[0031] (Liquid Crystal Polymer Web) A liquid crystal polymer web (LCP web) according to one embodiment of the present invention is a web containing liquid crystal polymer fibers (LCP fibers).

[0032] The LCP web preferably contains liquid crystal polymer fibers (LCP fibers) as a main component. In this specification, the term "main component" refers to the component that has the largest volume ratio of the main component to all components, and the ratio of the main component to all components is preferably 50 volume % or more and 90 volume % or less, more preferably 50 volume % or more and 80 volume % or less, and even more preferably 50 volume % or more and 70 volume % or less. The LCP web may be composed only of LCP fibers, or may contain LCP fibers and other materials.

[0033] The composite material (material other than LCP fiber) to be compounded with the LCP may be the main component of the LCP web. In this case, the ratio of the composite material to all components of the LCP web is preferably 50% by volume or more and 90% by volume or less (10% by volume or more and 50% by volume or less of LCP fiber), more preferably 50% by volume or more and 80% by volume or less (20% by volume or more and 50% by volume or less of LCP fiber), and even more preferably 50% by volume or more and 70% by volume or less (30% by volume or more and 50% by volume or less of LCP fiber).

[0034] In this specification, the term "web" refers to an assembly of LCP fibers on a sheet formed by depositing LCP fibers, and the LCP fibers are basically not bonded to each other, but may be partially bonded. For example, a web irradiated with a flash lamp is also included in the term "web" used here.

[0035] The thickness of the LCP web is not particularly limited, but is, for example, 5 μm or more and 250 μm or less.

[0036] The LCP web according to the present embodiment can be made into a film by pressing. This film may have copper foil bonded to at least one side, or may have copper foil bonded to both sides. The LCP film to which the copper foil is bonded can be used as a laminated molded product, for example, as FCCL (Flexible Copper Clad Laminates) that can be used to form a circuit by a subtractive method.

[0037] (Liquid Crystal Polymer Fiber) Liquid crystal polymer fibers (LCP fibers) are fibrous particles (materials) containing liquid crystal polymers as the main component. There are no particular limitations on the LCP fibers as long as they contain a fibrous portion. The fibrous portion may be linear or may have branches.

[0038] The average diameter of the LCP fibers (fibrous particles) in the powdered fine short fibers is preferably 2 μm or less, more preferably 1 μm or less, and the average aspect ratio of the LCP fibers is preferably 10 to 500, more preferably 300 or less, and even more preferably 100 or less.

[0039] The average diameter and average aspect ratio of the LCP fibers contained in the LCP powder are measured by the following method.

[0040] (Measurement of the average diameter and average aspect ratio of LCP fibers) LCP powder made of LCP fibers to be measured is dispersed in ethanol to prepare a slurry in which 0.01% by mass of LCP powder is dispersed. At this time, the slurry is prepared so that the water content in the slurry is 1% by mass or less. Then, 5 to 10 μL of this slurry is dropped onto a slide glass, and the slurry on the slide glass is allowed to dry naturally. By allowing the slurry to dry naturally, the LCP powder is arranged on the slide glass.

[0041] Next, a predetermined area of ​​the LCP powder placed on the slide glass is observed with a scanning electron microscope to collect 100 or more image data of the particles (LCP fibers) constituting the LCP powder. In collecting the image data, the area is set according to the size of each LCP particle so that the number of image data is 100 or more. In addition, in order to prevent the occurrence of missed image data collection or measurement errors for each LCP particle, the magnification of the scanning electron microscope is appropriately changed to 500x, 3000x, or 10000x to collect the image data.

[0042] Next, using the collected image data, the longitudinal dimension and width dimension of each of the LCP fibers are measured.

[0043] For one LCP fiber captured in each of the image data, the direction of the straight line connecting both ends of the longest path from one end of the fiber through approximately the center of the particle to the opposite end of the fiber is defined as the longitudinal direction. The length of the straight line connecting both ends of the longest path is measured as the longitudinal dimension.

[0044] In addition, the particle size in the direction perpendicular to the longitudinal direction is measured at three different points in the longitudinal direction of each particle of the LCP powder, and the average value of the dimensions measured at these three points is defined as the width direction dimension (fiber diameter) per particle of the LCP powder.

[0045] Furthermore, the ratio of the longitudinal dimension to the fiber diameter [longitudinal dimension / fiber diameter] is calculated to obtain the aspect ratio of the LCP fiber.

[0046] The average value of the fiber diameters measured for 100 LCP fibers is taken as the average diameter. The average aspect ratio is determined as the average value of the aspect ratios measured for 100 LCP fibers.

[0047] (Liquid Crystal Polymer: LCP) The liquid crystal polymer is not particularly limited, but examples thereof include thermotropic liquid crystal polymers.

[0048] The liquid crystal polymer is preferably free of amide bonds. Examples of thermotropic liquid crystal polymers free of amide bonds include copolymers of parahydroxybenzoic acid, terephthalic acid and dihydroxybiphenyl (copolymers of parahydroxybenzoic acid and ethylene terephthalate), which are called type 1 liquid crystal polymers and have a high melting point and low CTE, or copolymers of parahydroxybenzoic acid and 2,6-hydroxynaphthoic acid, which are called type 1.5 (or type 3) and have a melting point between type 1 liquid crystal polymers and type 2 liquid crystal polymers.

[0049] Each step of the manufacturing method of this embodiment will be described below. <Slurry preparation process: S1> The slurry preparation step (S1) is a step of preparing a slurry (LCP slurry) containing a dispersion medium and liquid crystal polymer fibers dispersed in the dispersion medium.

[0050] In the slurry preparation step, for example, LCP fibers (fibrous particles) in powdered fine short fibers are dispersed in a dispersion medium to prepare an LCP slurry.

[0051] Examples of the dispersion medium used in preparing the LCP slurry include water, ethanol, methanol, isopropyl alcohol, toluene, benzene, xylene, phenol, acetone, methyl ethyl ketone, diethyl ether, dimethyl ether, hexane, N,N-dimethylacetamide, tetrahydrofuran, diethylene glycol monohexyl ether, etc., or a mixture of at least two selected from these, etc. Among these, preferred dispersion media are water, ethanol, or a mixture thereof (aqueous ethanol solution).

[0052] The LCP powder used to prepare the LCP slurry may contain particles other than LCP fibers (particles that do not substantially contain fibrous parts, clumped particles formed by aggregation of LCP fibers, etc.), but the content (number ratio) of such particles is preferably 20% or less.

[0053] Furthermore, the LCP powder preferably has a D50 (average particle size) value of 13 μm or less, as measured by particle size measurement using a particle size distribution measuring device based on a laser diffraction scattering method.

[0054] In the slurry preparation step, the liquid crystal polymer fibers and a solid material different from the liquid crystal polymer fibers may be dispersed in the slurry. In this case, a composite containing the LCP fibers and the solid material is formed, and the composite is deposited to obtain a liquid crystal polymer web having high uniformity of dispersion of the LCP fibers and the solid material. In this case, the solid material used is preferably a material having high dispersibility in the dispersion medium of the slurry.

[0055] <Spray drying process: S2> The spray drying process is a process in which a slurry is sprayed and the sprayed slurry is dried by a drying gas.

[0056] In the spray drying step (S2), a specific method for spraying the slurry and drying the sprayed slurry with a drying gas can be, for example, a method in which the slurry is sprayed by a spray device 1 into a circulating drying gas 2 (hot air) (inside a chamber 3) as shown in FIG. 2, and then dried.

[0057] 3, the slurry may be spray-dried using a spray drying apparatus equipped with a spray device 13 having a two-fluid nozzle capable of spraying two independent types of fluid through a first nozzle 11 and a second nozzle 12. For example, the LCP slurry is sprayed from the first nozzle 11 and a drying gas 2 (such as heated N2 gas) is sprayed from the second nozzle 12, whereby the LCP slurry is spray-dried and a fine powder of LCP fibers is dispersed in a chamber below the spray device 13.

[0058] In the spray drying process, a solid material (powder, fibrous material, etc.) other than the liquid crystal polymer fiber may be dispersed in the drying gas. In this case, a composite containing the LCP fiber and the solid material is formed, and the composite is deposited to obtain a liquid crystal polymer web in which the LCP fiber and the solid material are highly uniformly dispersed.

[0059] Here, the solid material mixed in the drying gas preferably contains a material that has low dispersibility in the dispersion medium of the LCP slurry (low-dispersibility material).

[0060] In the case where LCP fibers and other solid materials are composited in an LCP web, if the solid material has high dispersibility in the dispersion medium of the LCP slurry, the solid material may be blended in the LCP slurry or the drying gas. If the solid material has low dispersibility in the dispersion medium of the LCP slurry, it is preferable to disperse the solid material in the drying gas. This is because, when a solid material with low dispersibility in the dispersion medium is blended in the LCP slurry, the dispersion uniformity of the solid material in the LCP web is low unless the surface of the material is treated or a dispersant is added to the dispersion medium.

[0061] For example, as one standard for dispersibility, 0.1% by volume of a solid material is added to a dispersion medium of 50 mL of 60% by mass aqueous ethanol solution in a 70 mL sample bottle (Kashiyo Co., Ltd. M-70), the sample bottle is shaken by hand 10 times, and then ultrasonic treatment is performed for 1 minute using a tabletop ultrasonic cleaner "UT206" (manufactured by Sharp Corporation, oscillation frequency: 37 kHz). Note that 0.1% by volume is the concentration of solid material in a slurry generally used in wet papermaking methods. If the presence of a solid material can be visually confirmed on the gas-liquid surface or bottom surface in the sample bottle after leaving it to stand for 1 minute, the solid material corresponds to a solid material that has low dispersibility in the dispersion medium (low dispersibility material).

[0062] The reason why a 60% by mass ethanol solution is used as the evaluation dispersion medium is that when the ethanol concentration exceeds 60 wt%, the ethanol solution becomes a hazardous material, making it extremely difficult to handle using the wet papermaking method. Materials that cannot be dispersed in a 60% by mass ethanol solution are difficult to compound with LCP fibers using the wet papermaking method, so the dry method is considered more suitable.

[0063] Examples of low-dispersibility materials include perfluoroalkoxyalkane (PFA), polytetrafluoroethylene (PTFE), FEP (Teflon: registered trademark), cycloolefin polymer (COP / COC), polyphenylene ether (PPE), syndiotactic polystyrene (SPS), polyether ether ketone (PEEK), bismaleimide, polynorbornene (PNB), hydrocarbon polymer materials, etc. However, the type of compound that falls under this low-dispersibility material may vary depending on the type of dispersion medium of the LCP slurry.

[0064] As an example, it has been confirmed by experiments that perfluoroalkoxyalkane (PFA) with an average particle size (D50) of 2 μm and polytetrafluoroethylene (PTFE) with an average particle size of 4 μm are low-dispersibility materials based on the above criteria in an ethanol aqueous solution containing 60% by mass of ethanol as a dispersion medium. Figure 6 shows photographs of dispersions of PFA (Figure 6(a)) and PTFE (Figure 6(b)) in a confirmation test of the above-mentioned low-dispersibility dispersion medium (after standing for 1 minute).

[0065] In the spray drying process, the drying gas may be reused. When the drying gas is N2 or the like, reusing the drying gas reduces environmental and cost burdens.

[0066] <Deposition process: S3> The depositing step is a step in which the spray dried liquid crystalline polymer fibers are deposited to form a web.

[0067] For example, as shown in Fig. 4, fine powder 4 of LCP fibers dispersed in the gas in chamber 3 by the spray drying process is sucked from below mesh 6 (conveyor mesh) to deposit the fine powder 4 of LCP fibers on mesh 6. As a result, deposit 5 is obtained.

[0068] In this way, by depositing the spray-dried LCP fibers in a state of minimal aggregation without causing them to re-aggregate, it is possible to obtain an LCP web in which the LCP fibers are highly uniformly dispersed.

[0069] A specific method for producing an LCP web from the deposit 5 includes, for example, a method in which a deposit of LCP fibers is subjected to instantaneous heat treatment using a flash lamp or the like. Such instantaneous heat treatment bonds the LCP fibers together, thereby producing an LCP web. When the LCP fibers are bonded together in this manner without applying pressure to the deposit, a bulky (high porosity) LCP web can be obtained. It is difficult to obtain such a bulky LCP web by conventional manufacturing methods (especially wet methods such as papermaking).

[0070] However, the method for producing an LCP web from the deposit 5 is not particularly limited, and depending on the application of the LCP web, the strength of the web may be increased to a level that allows it to be peeled off from the mesh by lightly heating or pressurizing the deposit 5. Alternatively, an LCP web may be produced by bonding LCP fibers together with an adhesive or the like.

[0071] The obtained LCP web may further be subjected to other steps, such as a pressing step and a winding step, as necessary.

[0072] According to the manufacturing method of the present embodiment described above, even when fine liquid crystal polymer fibers are used, a liquid crystal polymer web can be easily manufactured. This is because, in the manufacturing method of the present embodiment, fine LCP fibers do not scatter as in the dry method, and problems such as clogging of fine LCP fibers and air flow control are unlikely to occur as in the method described in Patent Document 1.

[0073] In addition, fine fibers and fibers that are easily charged, such as LCP fibers, tend to aggregate and form agglomerates. In conventional dry methods, it is difficult to defibrate the aggregates of LCP fibers in an air stream and thoroughly disperse the LCP fibers. In contrast, in a slurry state, the LCP fibers can be thoroughly dispersed by controlling wettability and stirring. By spray-drying a slurry in which the LCP fibers are well dispersed, the dry powder of the LCP fibers is made to exist in a well-dispersed state in the gas, and an LCP web can be produced from the deposit that maintains the dispersed state. This makes it possible to obtain an LCP web in which the LCP fibers are highly uniformly dispersed, regardless of the size or chargeability of the LCP fibers.

[0074] Furthermore, in the manufacturing method of this embodiment, a slurry of LCP fibers at a higher concentration than in the papermaking method is spray-dried and the LCP fibers dispersed in the gas phase are directly deposited (without being collected), thereby making it possible to reduce the amount of solvent used to about 1 / 10 compared to the papermaking method.

[0075] <How to prepare liquid crystal polymer powder> The following describes in detail the method for producing an example of the liquid crystal polymer powder used in the above-mentioned slurry preparation process. The liquid crystal polymer powder can be produced, for example, by carrying out the following coarse pulverization process, fine pulverization process, coarse particle removal process, and fiberization process in this order.

[0076] The form of the raw material (LCP raw material) made of liquid crystal polymer used to prepare the liquid crystal polymer powder can be, for example, a biaxially oriented film or web, a uniaxially oriented pellet, a powder, etc. The LCP constituting the LCP raw material is the same as the LCP constituting the above-mentioned LCP fiber.

[0077] (Coarse grinding process) In the coarse pulverization step, the LCP raw material is coarsely pulverized. For example, the LCP raw material is coarsely pulverized with a cutter mill. The size of the coarsely pulverized LCP particles is not particularly limited as long as it can be used as a raw material for the fine pulverization step described later. The maximum particle size of the coarsely pulverized LCP particles is, for example, 3 mm or less.

[0078] It is not always necessary to carry out the coarse pulverization step. For example, if the LCP raw material can be used as a raw material for the fine pulverization step, the LCP raw material may be used directly as a raw material for the fine pulverization step.

[0079] (Fine grinding process) In the fine pulverization step, the LCP raw material (after the coarse pulverization step) is pulverized while being dispersed in liquid nitrogen to obtain granular finely pulverized liquid crystal polymer (finely pulverized LCP).

[0080] In the pulverization step, it is preferable to use media to pulverize the LCP raw material dispersed in liquid nitrogen. The media is, for example, beads. In the pulverization step of this embodiment, it is preferable to use a bead mill, which has relatively few technical problems, from the viewpoint of handling liquid nitrogen. An example of a device that can be used in the pulverization step is the liquid nitrogen bead mill "LNM-08" manufactured by IMEX.

[0081] The granular finely pulverized LCP obtained by the fine pulverization process preferably has a D50 of 50 μm or less as measured by a particle size distribution measuring device using a laser diffraction scattering method, which can prevent the granular finely pulverized LCP from clogging the nozzle in the fiberization process described below.

[0082] (Coarse particle removal process) Next, in the coarse particle removal step, coarse particles are removed from the granular pulverized LCP obtained in the pulverization step. For example, the granular pulverized LCP is sieved through a mesh to obtain granular pulverized LCP that falls below the sieve, and the granular liquid crystal polymer that remains above the sieve is removed to remove the coarse particles contained in the granular pulverized LCP. The type of mesh may be appropriately selected, and an example of the mesh is one with an opening of 53 μm. The coarse particle removal step is not necessarily required.

[0083] (Fiberization process) Next, in the fiberization process, the granular liquid crystal polymer is crushed by a wet high-pressure crushing device to obtain a liquid crystal polymer powder. In the fiberization process, the finely pulverized LCP is first dispersed in a dispersion medium for the fiberization process. The finely pulverized LCP to be dispersed does not need to have coarse particles removed, but it is preferable that the coarse particles have been removed. Examples of the dispersion medium for the fiberization process include water, ethanol, methanol, isopropyl alcohol, toluene, benzene, xylene, phenol, acetone, methyl ethyl ketone, diethyl ether, dimethyl ether, hexane, or a mixture thereof. The dispersion medium used in this fiberization process is preferably the same as the dispersion medium of the above-mentioned LCP slurry.

[0084] Then, the finely pulverized LCP dispersed in the dispersion medium for the fiberization process, i.e., the finely pulverized LCP in a paste or slurry state, is passed through a nozzle under high pressure. By passing through the nozzle under high pressure, the shear force or collision energy due to the high-speed flow in the nozzle acts on the liquid crystal polymer, crushing the granular finely pulverized LCP, and fiberization of the liquid crystal polymer progresses, and a liquid crystal polymer powder consisting of fine LCP fibers can be obtained. From the viewpoint of applying high shear force or high collision energy, it is preferable that the nozzle diameter of the nozzle is as small as possible within a range in which clogging of the finely pulverized LCP does not occur in the nozzle. Since the particle diameter of the granular finely pulverized LCP is relatively small, the nozzle diameter of the wet high-pressure crushing device used in the fiberization process can be made small. The nozzle diameter is, for example, 0.2 mm or less.

[0085] As described above, a plurality of fine cracks are formed in the granular pulverized LCP. Therefore, the dispersion medium penetrates into the inside of the pulverized LCP through the fine cracks by pressurization in the wet high-pressure crushing device. Then, when the paste-like or slurry-like pulverized LCP passes through the nozzle and is placed under normal pressure, the dispersion medium that penetrates into the inside of the pulverized LCP expands in a short time. The expansion of the dispersion medium that penetrates into the inside of the pulverized LCP causes destruction to proceed from the inside of the pulverized LCP. Therefore, fiberization proceeds to the inside of the pulverized LCP, and the liquid crystal polymer molecules are separated into domain units in which they are aligned in one direction. Thus, in the fiberization process in this embodiment, by defibrating the granular pulverized LCP obtained in the pulverization process in this embodiment, a liquid crystal polymer powder having a lower content of clumped particles and consisting of fine LCP fibers can be obtained, compared to the liquid crystal polymer powder obtained by crushing the granular liquid crystal polymer obtained by the conventional freeze-pulverization method.

[0086] In the fiberization process in this embodiment, the finely pulverized LCP may be crushed multiple times by a wet high-pressure crushing device to obtain liquid crystal polymer powder. However, from the viewpoint of production efficiency, it is preferable to crush the liquid crystal polymer powder by the wet high-pressure crushing device a small number of times, for example, 5 times or less. EXAMPLES

[0087] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these.

[0088] <Example 1> (Slurry preparation process: S1) First, an LCP film (melting point: 315°C, thickness: 250μm) with molecules oriented biaxially in the plane direction was prepared as the LCP raw material. The LCP material is a copolymer of parahydroxybenzoic acid and 4,6-hydroxynaphthoic acid.

[0089] This LCP raw material was coarsely pulverized using a cutter mill (MF10 manufactured by IKA). The coarsely pulverized LCP was passed through a mesh with 3 mm openings provided at the outlet of the cutter mill to obtain coarsely pulverized LCP.

[0090] Next, the coarsely pulverized LCP was finely pulverized in a liquid nitrogen bead mill (LNM-08, manufactured by IMEX, vessel capacity: 0.8 L). Specifically, 500 mL of media and 30 g of the coarsely pulverized LCP were placed in a vessel, and pulverization was performed for 120 minutes at a rotation speed of 2000 rpm. Zirconia (ZrO2) beads with a diameter of 5 mm were used as the media. In the liquid nitrogen bead mill, the coarsely pulverized LCP was dispersed in liquid nitrogen, and wet pulverization was performed. In this way, the coarsely pulverized LCP was pulverized in the liquid nitrogen bead mill to obtain granular finely pulverized LCP.

[0091] The particle size distribution of this finely ground LCP was measured. In the particle size measurement, the finely ground LCP dispersed in the dispersion medium was subjected to ultrasonic treatment for 10 seconds, and then set in a particle size distribution measuring device (LA-950, manufactured by Horiba, Ltd.) using a laser diffraction scattering method to measure the particle size distribution. As the dispersion medium, Ekinen (registered trademark, Japan Alcohol Sales Co., Ltd.), a mixed solvent mainly composed of ethanol, was used. The measured value of D50 of the finely ground LCP was 23 μm.

[0092] Next, the dispersion liquid obtained by dispersing the finely pulverized LCP in the equene was sieved through a mesh with an opening of 53 μm to remove the coarse particles contained in the finely pulverized LCP, and the finely pulverized LCP that passed through the mesh was collected. The yield of the finely pulverized LCP after removing the coarse particles was 85% by mass.

[0093] Next, the finely pulverized LCP from which the coarse particles had been removed was dispersed in a 20% by mass ethanol solution. The ethanol slurry in which the finely pulverized LCP was dispersed was repeatedly crushed five times using a wet high-pressure crushing device under conditions of a nozzle diameter of 0.18 mm and a pressure of 200 MPa, to form fibers. As the wet high-pressure crushing device, a high-pressure disperser (Starburst Lab, manufactured by Sugino Machine) was used. This resulted in the preparation of a slurry in which the LCP powder (LCP fiber) was dispersed in an ethanol aqueous solution. This slurry was further diluted with an ethanol aqueous solution (ethanol concentration: 50% by mass) so that the LCP concentration became 1% by mass. This resulted in the preparation of an LCP slurry to be used in the next spray drying process.

[0094] (Spray drying process: S2) The LCP slurry prepared as described above was spray-dried. Specifically, spray drying was performed using a spray drying apparatus equipped with a spray device 13 having a two-fluid nozzle capable of ejecting two independent fluids from a first nozzle 11 and a second nozzle 12 as shown in Fig. 3. That is, the LCP slurry was sprayed from the first nozzle 11, and N2 gas heated to 180°C was ejected from the second nozzle 12 as a drying gas, whereby the LCP slurry was spray-dried, and a fine powder of LCP fibers was dispersed in the chamber below the spray device 13.

[0095] (Deposition process: S3) A mesh with an opening of 11 μm (manufactured by Kureha Co., Ltd.) was placed 40 cm below the spray device 13, and by suction from below the mesh, the fine powder of LCP fibers dispersed in the chamber was deposited on the mesh. After a predetermined amount of LCP fibers had been deposited, the mesh was removed (see Figure 4).

[0096] The LCP fiber deposit on the removed mesh was subjected to a heat treatment with a flash lamp to bond the LCP fibers on the surface to each other so that the fibers had sufficient strength to be peeled off from the mesh, thereby producing an LCP web. The obtained LCP web was peeled off from the mesh to obtain the LCP web of Example 1. The thickness of the obtained LCP web was approximately 100 μm (FIG. 5).

[0097] <Example 2> The same slurry as in Example 1 is sprayed under the same conditions. In this case, in the spray drying process, a powder of PFA particles having an average particle size (D50) of 2 μm is dispersed in the drying gas so as to have a concentration of 30% by volume. Otherwise, an LCP web is produced in the same manner as in Example 1. The obtained composite web shows good dispersibility of PFA (see FIG. 7). Note that FIG. 7 is a cross-sectional photograph of the composite web of Example 2, and the portion shown by the diagonal hatching in FIG. 7 is PFA. A film obtained by enriching this web (after pressing) also shows good dispersibility of PFA compared to Comparative Example 1 (FIG. 11) described later (see FIG. 8). FIG. 8 is a cross-sectional photograph of the above film.

[0098] <Example 3> A composite web was prepared in the same manner as in Example 2, except that the powder of PFA particles was changed to PTFE. The composite web deposited under these conditions showed good dispersibility of PTFE (see FIG. 9). Note that FIG. 9 is a cross-sectional photograph of the composite web of Example 3, and the portion indicated by the diagonal hatching in FIG. 9 is PTFE.

[0099] <Example 4> The slurry of Example 1 was added with 30% by volume of hydrophilically treated PFA, which was then deposited through a spray drying process to form a web. The composite web deposited under these conditions showed good dispersibility of PFA (see FIG. 10). Note that FIG. 10 is a cross-sectional photograph of the composite web of Example 4, and the portion hatched with diagonal lines in FIG. 10 is PFA.

[0100] For the hydrophilic treatment, a powder plasma treatment device manufactured by Sakigake Semiconductor Co., Ltd. was used to perform surface treatment until the PFA was mixed and dispersed in the aqueous solution. The powder plasma treatment device is a device that performs atmospheric pressure plasma treatment in liquid, and is a dielectric barrier discharge plasma device that uses water as a dielectric. In this way, a dispersion of hydrophilically treated PFA was obtained.

[0101] <Example 5> Except for changing the powder of PFA particles to polynorbornene, a composite web was produced in the same manner as in Example 2. The composite web deposited under these conditions showed good dispersibility of polynorbornene.

[0102] <Comparative Example 1> The cross-sectional state of a film formed by melt extrusion of LCP and PFA is shown in Figure 11. Severe aggregation of PFA is evident.

[0103] <Comparative Example 2> The LCP slurry prepared in the same manner as in the slurry preparation step of Example 1 was diluted with an aqueous ethanol solution (ethanol concentration: 50% by mass) so that the LCP concentration became 0.1% by mass. The LCP web of Comparative Example 2 was prepared by a square papermaking method (wet method) using this diluted LCP slurry.

[0104] <Comparative Example 3> The LCP fibers produced by spraying in the same manner as in the slurry preparation step of Example 1 were collected, sieved through a 150 μm mesh sieve (manufactured by Sanpo), and piled up in an attempt to form a web. However, the LCP fibers were agglomerated and could not be passed through the sieve, and an LCP web could not be produced.

[0105] [LCP ​​Web Observation] A sample for observation was prepared by filling the LCP web (web) obtained in Example 1 and Comparative Example 2 with a resin, and then solidifying the resin, and the sample was polished to prepare a cross section (a surface parallel to the thickness direction). The polished cross section was further processed by CP (chemical polishing), and then the polished cross section was observed with a scanning microscope.

[0106] FIG. 5 is a photograph (scanning electron microscope image) of the cross section (plane parallel to the thickness direction of the web) of the LCP web in Example 1 (top) and Comparative Example 2 (bottom). The numbers at the top of the photographs in FIG. 5 indicate the magnification of the microscope. From the photographs in FIG. 5, it can be seen that in Example 1, a web with highly uniform dispersion of LCP fibers was produced. It can also be seen that the LCP web of Example 1 is bulkier (has a larger void ratio) than the LCP web produced by the papermaking method of Comparative Example 2.

[0107] In the above description of the embodiments, configurations that can be combined may be combined with each other.

[0108] The embodiments and examples disclosed herein should be considered to be illustrative and not restrictive in all respects. The scope of the present invention is defined by the claims, not the above description, and is intended to include all modifications within the meaning and scope of the claims. [Explanation of symbols]

[0109] 1,13 spray device, 11 first nozzle, 12 second nozzle, 2 drying gas, 3 chamber, 4 fine powder of LCP fiber, 5 deposit, 6 mesh.

Claims

1. A slurry preparation step of preparing a slurry containing a dispersion medium and liquid crystal polymer fibers dispersed in the dispersion medium; a spray drying step of spraying the slurry and drying the sprayed slurry with a drying gas; depositing the spray dried liquid crystalline polymer fibers to form a web; Equipped with The average diameter of the liquid crystal polymer fibers is 2 μm or less, The average aspect ratio of the liquid crystal polymer fibers is 10 or more and 500 or less.

2. A slurry preparation step of preparing a slurry containing a dispersion medium and liquid crystal polymer fibers dispersed in the dispersion medium; a spray drying step of spraying the slurry and drying the sprayed slurry with a drying gas; depositing the spray dried liquid crystalline polymer fibers to form a web; Equipped with In the spray drying step, a solid material different from the liquid crystal polymer fibers is dispersed in the drying gas.

3. The method according to claim 2 , wherein the solid material includes a material that is poorly dispersible in the dispersion medium in the slurry.

4. A method for producing a slurry comprising: preparing a dispersion medium and liquid crystal polymer fibers dispersed in the dispersion medium; a spray drying step of spraying the slurry and drying the sprayed slurry with a drying gas; depositing the spray dried liquid crystalline polymer fibers to form a web; Equipped with In the slurry preparation step, the liquid crystal polymer fibers and a solid material different from the liquid crystal polymer fibers are dispersed in the slurry.

5. The method according to claim 2 , wherein in the slurry preparation step, the liquid crystal polymer fibers and a solid material different from the liquid crystal polymer fibers are dispersed in the slurry.

6. The method according to any one of claims 1 to 5, wherein the drying gas is reused in the spray drying step.

Citation Information

Patent Citations

  • Method for preparing polymeric nano-micro fiber non-woven fabric

    CN102071542A

  • Fiber,roving and mat prepared from synthetic liquid crystal polymer

    JP1990234909A

  • Wet-laid nonwoven fabric

    JP2003129392A

  • Sheet, sheet production apparatus and sheet production method

    JP2018145574A

  • Resin composition for printed circuit boards and production method

    JP2019065061A